Cornstalk round bale processing method does not influence feeding characteristics or feed refusals - S.Q. Jones; T.T. Marston; T.J. Kraus; Joel M. DeRouchey; Justin W. Waggoner; Ryan M. Breiner (Kansas Agricultural Experiment Station Research Reports, 2010)
Nutritionists and producers often assume that ingredients in a total mixed ration are uniformly mixed. However, many factors can affect ration homogeneity, including particle size, particle shape, differences in density of feed ingredients, and relative point at which the mixture is discharged from a mixer batch. Forages often are ground prior to mixing in a total mixed ration to reduce variation in forage particle length. Preprocessing forages during baling may facilitate particle length reduction, eliminating the need to grind forages prior to mixing. The objectives of this study were to determine the effects of forage processing on (1) uniformity of the ration discharged from the mixer at different points, (2) particle length throughout the mixing process by bale type, and (3) difference in feed refusals of mixed rations based on forages processed by different methods.
Keywords: Cattlemen' s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen' s Day; Beef; Cornstalk bales; Feed characteristics; Dry matter intake